2023
DOI: 10.3390/cryst13010075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Gemological and Mineralogical Characteristics and Coloration Mechanism of Four Color Types of Fluorite

Abstract: Fluorite has been attracting the attention of gemstone mineralogists because of its rich color and excellent fluorescence properties. This paper studied fluorite with three color types (blue, green, and white) and five blue-purple fluorites with an alexandrite effect. Through the study of their structure, composition, and spectral characteristics, the gemological and mineralogical characteristics and coloration mechanisms of different color types of fluorites are compared and analyzed. The results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Studies by Tsuda et al [18] elucidated that this Raman signal corresponds to the CaF 2 lattice vibration at 322 cm ¹. Russell [19] obtained Raman peak of uorite at 322 cm − 1 . Additionally, Liu et al [20] reported a Raman peak at 320 cm − 1 for white uorite. Lewandowski et al [21] observed Raman peak at 319.13 cm − 1 for calcium uoride.…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…Studies by Tsuda et al [18] elucidated that this Raman signal corresponds to the CaF 2 lattice vibration at 322 cm ¹. Russell [19] obtained Raman peak of uorite at 322 cm − 1 . Additionally, Liu et al [20] reported a Raman peak at 320 cm − 1 for white uorite. Lewandowski et al [21] observed Raman peak at 319.13 cm − 1 for calcium uoride.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Consequently, the PL emission peak of uorites from different areas under a short wave is mainly at 510 nm, and the intensity is weak [20]. The presence of the Yttrium (Y) element is considered one of the reasons why uorite exhibits uorescence [20], [36][37][38][39][40]. According to Table 2, the concentrations of Y in samples E, EB, FB, and G are recorded as 1.5, 0.6, 3.4, and 2 ppm, respectively.…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations